Optimalisasi Keselamatan dan Efisiensi Layanan Wisata melalui Implementasi Papan Alur Digital Berbasis ESP32 - Riskitasari, Septyana; Supriyanto, Nicky Suwandhy Widhi; Ekasari, Silvia Rahmi; Sari, Nurlia Pramita; Machfuroh, Talifatim; Perkasa, Rilis Eka (Welfare : Jurnal Pengabdian Masyarakat, 2026)
Banyumaro River Tubing faces high workloads on guides due to repetitive verbal safety briefings for 50–60 visitors weekly. This community service project addressed the issue by developing a digital flow panel as an interactive safety education tool before tubing. Using the Asset-Based Community Development (ABCD) approach, the system was collaboratively designed with an ESP32 microcontroller, neon LED lights, and audio modules that activate sequentially. Results show the panel delivers consistent information, reduces guide workload, and enhances operational efficiency and visitor safety. This innovation supports sustainable, community-based tourism development through appropriate technology and local empowerment.